2018
DOI: 10.1186/s11671-017-2431-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Synthesis Method of La1 − xSrxMnO3 Manganite Nanoparticles on Their Properties

Abstract: Nanoparticles of lanthanum-strontium manganite were synthesized via different methods, namely, sol-gel method, precipitation from non-aqueous solution, and precipitation from reversal microemulsions. It was shown that the use of organic compounds and non-aqueous media allowed significantly decreasing of the crystallization temperature of nanoparticles, and the single-phased crystalline product was formed in one stage. Morphology and properties of nanoparticles depended on the method and conditions of the synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Ultraviolet or infrared radiation is able to make graphene sensitive to different types of gases, allowing for certain selectivity. However, the light adsorption efficiency of graphene is weak [ 75 , 76 ]. The selective capabilities of graphene can be easily enhanced by grafting functional groups on its surface.…”
Section: Functionalized Graphene Nh 3 Sensorsmentioning
confidence: 99%
“…Ultraviolet or infrared radiation is able to make graphene sensitive to different types of gases, allowing for certain selectivity. However, the light adsorption efficiency of graphene is weak [ 75 , 76 ]. The selective capabilities of graphene can be easily enhanced by grafting functional groups on its surface.…”
Section: Functionalized Graphene Nh 3 Sensorsmentioning
confidence: 99%
“…Nanoparticles of lanthanum strontium manganite La 1−x Sr x MnO 3 with x = 0.23, denoted as LSMO in the rest of the text, were synthesized by solgel method according to the route described in [40,41]. Briefly, watersoluble metal salts La(NO 3 ) 3 •6H 2 O, Mn(NO 3 ) 2 •4H 2 O and Sr(NO 3 ) 2 were used as starting materials.…”
Section: Synthesis and Structural Charactirizationmentioning
confidence: 99%
“…For example, a solid-state reaction method occurs at high temperatures (> 1000 °C), which results in non-porous, irregular powder products, uncontrolled particle size, and low surface area (Kaewpanha et al 2019 ). Other interesting chemical approaches in low sintering temperature and short reaction time (Li et al 2019b ), such as the sol–gel process and co-precipitation, have been reported to prepare materials with improved control of grain size and uniform particle size distribution and morphology (Hannora and Hanna 2019 , Ghozza et al 2013 , Shlapa et al 2018 ). Therefore, by the co-precipitation method, we focus on preparing La 0.7 Sr 0.3 MnO 3 and La 0.7 Sr 0.3 CoO 3 , but the sol–gel auto-combustion route to prepare La 0.7 Sr 0.3 FeO 3 samples.…”
Section: Introductionmentioning
confidence: 99%